Measuring unification - Adam, Claire; Kneur, Jean-Loic; Lafaye, Rémi; Plehn, Tilman; Rauch, Michael; Zerwas, Dirk (The European physical journal. C, Particles and fields, 2011)
If supersymmetry is observed at the LHC its model parameters can be measured at the electroweak scale. We discuss the expected precision on the parameter determination, including a proper treatment of experimental and theoretical errors. Particular attention is paid to degenerate solutions. Using the SFitter framework we perform a bottom-up reconstruction of the unified parameters at the high scale, including a full error propagation.